2012
DOI: 10.1016/j.electacta.2012.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Redox switching of Prussian blue thin films investigated by ac-electrogravimetry

Abstract: of Prussian blue thin films investigated by ac-electrogravimetry. Electrochimica Acta, Elsevier, 2012, 84, pp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…in any state, which means that there are no possibilities of dissolving from titanium mesh current collector or the NaTi 2 (PO 4 ) 3 anode. As shown in 27,31,32 At the charged state up to 0.9 V in 1 m NaClO 4 aq., detected metal ions amount in the electrolyte and the coloration did not change much compared to the initial state, but pH value shifted from 4 to 6. H + concentration is not increased, because the voltage of NMHCF cathode is much lower than the potential of O 2 evolution as shown in Fig.…”
Section: Electrolyte Properties During Charge/discharge Processmentioning
confidence: 99%
“…in any state, which means that there are no possibilities of dissolving from titanium mesh current collector or the NaTi 2 (PO 4 ) 3 anode. As shown in 27,31,32 At the charged state up to 0.9 V in 1 m NaClO 4 aq., detected metal ions amount in the electrolyte and the coloration did not change much compared to the initial state, but pH value shifted from 4 to 6. H + concentration is not increased, because the voltage of NMHCF cathode is much lower than the potential of O 2 evolution as shown in Fig.…”
Section: Electrolyte Properties During Charge/discharge Processmentioning
confidence: 99%
“…It can be reduced from its deep blue color to the colorless form of Prussian white (PW) and then recovered by oxidation through the following reaction: KFe 3+ [Fe 2+ (CN) 6 ] + K + + e − ⇄ K 2 Fe 2+ [Fe 2+ (CN) 6 ]. 34 Because of its excellent color switching properties between PB and PW under external electrical stimuli, PB has been considered as a prominent candidate for the electrochromic displays. Previous studies on these electrochromic devices have reported lifetimes in the range of 10 5 to over 10 7 cycles, suggesting extremely high stability for color switching.…”
mentioning
confidence: 99%
“…The result that is presented in Figure 11 indicates that the potential response remained constant at the pH range of 2.0-10.0, which can be used as the applicable pH range of the prepared electrode. At pH <2.0, the response potential of bromide electrode significantly decreased with decreasing pH values due to the simultaneous response of the electrode to the oppositely charged H 3 O + and Br − [51]. When the pH is greater than 10, on the contrary, OH − strongly competed with Br − to form oxonium cations, which resulted in an augmented response potential with increasing pH values [52].…”
Section: Effect Of Ph and Selectivitymentioning
confidence: 99%